Satisfaction: The Determinant of Tourist Destination Familiarity [Satisfacción: Determinante de la Familiaridad del Destino Turístico] - Marinao-Artigas, E (Fundacao Getulio Vargas, 2014)
This study aims to prove the satisfaction felt by a tourist is the result of the functional, hedonic and symbolic benefits acquired from the site. In its turn, it aims to prove that satisfaction is an antecedent for the tourist destination to become more familiar. Different scales are identified to permit measuring these relations based on a confirmatory factor analysis (CFA). A non-probabilistic sample was used based on quotas, in the proportion of tourist destinations visited in Chile. The relationship between perceiving benefits as antecedents for satisfaction can be very important for the tourist destination to be perceived as more familiar than other destinations. This study suggests that satisfaction complies with a very important mediator function between the perception of benefits and the familiarity of the tourist destination. Authorities should consider the triad of benefits as a basis for establishing marketing strategies that seek an increase in satisfaction. © RAE.